2018
DOI: 10.1155/2018/3078031
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of the Appendix Testis in Normal Testicular Descent: Is There a Connection?

Abstract: Objective The presence of testicular appendices was prospectively evaluated in 89 boys with 96 undescended testes who underwent orchidopexy over the period of 4 years. Results The patients were divided into two groups. Group A included 42 boys with 49 undescended testes positioned close to the internal inguinal ring, and Group B included 47 boys with 47 undescended testes close to the external inguinal ring. The incidence of appendix testis (AT) in Group A was 57.1% (28 in 49) and 78.7% (37 in 47) in Group B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
3
1
Order By: Relevance
“…In turn, in hydrocele patients we noted the significantly higher incidence of testis/epididymis appendices in comparison to the UDT patients. This is in line with studies which have hypothesized about the possible role of the appendix testis in testicular descent, noticing a reduced incidence of appendix testis among boys with UDT compared to boys without testicular maldescent [ 31 , 32 ]. The testis appendix was considered as an organ taking part in fluid regulation within the vaginal tunica space [ 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…In turn, in hydrocele patients we noted the significantly higher incidence of testis/epididymis appendices in comparison to the UDT patients. This is in line with studies which have hypothesized about the possible role of the appendix testis in testicular descent, noticing a reduced incidence of appendix testis among boys with UDT compared to boys without testicular maldescent [ 31 , 32 ]. The testis appendix was considered as an organ taking part in fluid regulation within the vaginal tunica space [ 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…This possibility needs to be explored further in cadaver parts or testes submitted to orchiectomy. The frequency of gonadal appendix in our series (44.5% in the testes and 22.2% in the epididymes) was lower than the reported by Zdizvic [ 11 ], who described a frequency of 78.7% in gonads located close to the external inguinal ring in 89 normal boys. All operated testes of our series were palpable close to the external inguinal ring.…”
Section: Discussioncontrasting
confidence: 83%
“…Favorito et al ( 23 ) found that the probabilities of the processus vaginalis patency of intra-abdominal and intracanalicular testes were 100% (14/14) and 64.2% (52/81), respectively. Zvizdic et al ( 24 ) suggested that 61.2% of the affected side of UDT near the internal ring had patency of the processus vaginalis patency. Our findings were largely consistent with previous findings (intra-abdominal vs. inguinal, 92.9 vs. 72.9%).…”
Section: Discussionmentioning
confidence: 99%